Professional experience before a PhD. Does it pay off? - Cadilhe, Maria; Almeida, Beatriz; Rodrigues, Ana I.; Santos, Marta (Frontiers in Education, 2023)
The number of PhD graduates has been increasing yearly, but the job opportunities in Academia remain the same. This pattern will intensify the pressure on PhD students to look for other possible careers. Past work experiences, due to their developmental potential, occupy a prominent place in the career development paradigm. However, more is needed to know about the professional path of PhD students before they entered the PhD. This study aimed to explore PhD students' previous professional experience, focusing on the extent to which previous experiences determine students' perception and development of career expectations. A quantitative research approach was followed among 377 PhD students at a Portuguese Higher Education Institution (HEI). Results show that regardless of their previous work experiences, PhD students value career options related to research, preferably within Academia. However, in terms of career development, students who have diverse work experiences reported feeling more prepared to put into practice actions to prepare their career than students with professional experience in Academia or no professional experience. This study confirms that PhD students’ previous work experiences pay off by making a difference in the feeling of preparedness for career development, whereas in terms of student’s future career expectations after the PhD, it did not allow for a definite answer, as it seems that all professional groups prefer similar research-oriented paths. Intervention must be done simultaneously on individual and contextual level, allowing students to have experiences during the PhD and promoting the reflection on the experiences so students may feel more prepared to develop their future careers. For companies, it should focus on showing the PhDs’ added value and also the potential of incorporating the R&D dimensions within their jobs. Failing to do so may contribute to enhancing the employability challenges faced by the growing number of PhD holders.